Zróżnicowane programy aktywizujące a sprawność funkcjonalna kobiet w wieku 60+ = Diverse activation programs and the efficiency of functional women aged 60+ - Katarzyna Prusik; Zbiegniew Ossowski; Łukasz Bielawa; Monika Wiech; Jakub Kortas; Seweryna Konieczna; Krzysztof Prusik (Kazimierz Wielki University, 2016)
Prusik Katarzyna, Ossowski Zbigniew, Bielawa Łukasz, Wiech Monika, Kortas Jakub, Konieczna Seweryna, Prusik Krzysztof. Zróżnicowane programy aktywizujące a sprawność funkcjonalna kobiet w wieku 60+ = Diverse activation programs and the efficiency of functional women aged 60+. Journal of Education, Health and Sport. 2016;6(3):113-124. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47867 http://ojs.ukw.edu.pl/index.php/johs/article/view/3425 https://pbn.nauka.gov.pl/works/721251   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.     Zróżnicowane programy aktywizujące a sprawność funkcjonalna kobiet w wieku 60+   Diverse activation programs and the efficiency of functional women aged 60+   Katarzyna Prusik1, Zbigniew Ossowski1, Łukasz Bielawa1, Monika Wiech1, Jakub Kortas1, Seweryna Konieczna2, Krzysztof Prusik1   1Academy of Physical Education and Sport in Gdansk 2Medical University of Gdansk   Keywords: Nordic Walking, health training, occupational therapy. Słowa kluczowe: Nordic Walking, trening zdrowotny, terapia zajęciowa.   Abstract One of the many forms of activity may be physical activity dressed in costume popular in Poland and in the world of Nordic Walking. Another way to stimulate the occupational therapy, which involves the realm of the physical, mental and social man usually less active in general. The objectives of occupational therapy are similar to the general objectives underlying any form of physical activity, and that is the behavior of self-reliance, independence and efficiency. The aim of the study is to analyze different activation programs in relation to the functional capacity of women aged 60+. We analyzed two fundamentally different activation programs seniors: occupational therapy program implemented in the Daily Nursing Home for the Elderly in Gdansk and health training program in the form of Nordic Walking realized within statutory research. The material tested is 48 women over the age of 60, after 24 people training Nordic Walking 3 times a week for 60 minutes, and 24 people participating in occupational therapy. Physical activity is an effective means to maintain physical for a long time, it can also be an effective means of shaping it during aging. Physical activity should begin early. Then you can expect spectacular effects of training, and thus a high physical translates directly to high levels of positive physical health. You can expect to achieve in this area, the leader among his peers. You can go ahead and prepare for old age, efficient, independent and self.